The Influence Of Spiritual Cognitive Therapy Murattal Al-Qur'an (Surah Ar-Rahman) On Postpartum Blues In The RSUD Subang - Queen Tahtana; Fitri Handayani; Novian Mahayu (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Introduction: The incidence of postpartum blues is a change in the mother's psychology which is influenced by fatigue factors that arise after the birth and breastfeeding process. This can influence changes in the routine of caring for the baby which requires extra attention from the mother. Handling postpartum blues can use spiritually based non-pharmacological techniques in the Islamic religion using murattal Al-Qur'an. This study aims to determine the influence of spiritual cognitive therapy murattal Al-Qur'an (Surah Ar-Rahman) on the incidence of postpartum blues in RSUD SUBANG. Methods: This research method is quantitative with a quasi-experimental design with pre and post with control group. The number of respondents in this study was 24 in the intervention group and 24 in the control group. Data collection for this research used the EPDS scale (Edinburgh Postpartum Depression Scale) with data analysis using the Wilcoxon test and the Man-Whittney test. Result: The results of this study showed a difference in the pre-test and post-test of the intervention group with p = 0.000. It can be concluded that spiritual cognitive therapy murattal Al-Qur'an (Surah Ar-Rahman) has an influence on the incidence of postpartum blues in RSUD Subang. It is hoped that this research will further investigate more deeply and be able to control confounding variables that might interfere with the influence of the Murattal Al-Qur'an spiritual cognitive therapy (Surah Ar-Rahman) on the incidence of postpartum blues.